Pengaruh Diuretik Terhadap Stone-Free Rate Batu Ureter dengan Pneumatic Lithotripsy - Muhammad Ridha; Dahril; Rayyan Al Faruqi; Muyasir; Jufriady Ismy (LITBANG RSUDZA, 2022)
Pneumatic Lithotripsy (PL) is considered effective in fragmenting hard stones, and this procedure can also be performed transurethrally and percutaneously on large stones. This study aimed to see the percentage of Stone Free Rate (SFR) by administering force diuretics to ureteral stones that were crushed using PL. Previous studies have found that intravenous loop diuretic administration is effective, safe, and efficient in obtaining a much higher percentage of SFR and can reduce the average number of sessions per stone during extracorporeal shock wave lithotripsy (ESWL). We identified study subjects from early July-September 2022 and obtained as many as 38 study subjects (SP) with stones in the distal ureter <20mm. Subjects were randomly selected and divided into two groups: the group given diuretics (K2) and not given (K1). With a 90% confidence degree and 15% sampling error, based on Lameshow's formula, 30 SP can be observed; eight other subjects were excluded because they experienced a decrease in systolic pressure >25% (5 SP) and the remaining stones came out without splitting (3SP). The results obtained were SFR levels that were statistically significant (p<0.05) and clinically using the Mann-Whitney statistical test. Administration of diuretics to patients with distal ureteral stones undergoing URS with Pneumatic Lithotripsy is safe and effective as an anti-retropulsion method. It is the strategy of choice in centers that do not provide laser lithotripsy or flexible ureteroscope.